HUBUNGAN SENAM HAMIL DENGAN PERSALINAN NORMAL DI BPM ERNITA KOTA PEKANBARU TAHUN 2018 - silvia nova nova; Een Mardiani (Jurnal Ilmu Kebidanan, 2019)
Childbirth is a physiological thing experienced by the mother. Every mother wants her childbirth to be proceed normally. Factors that influence childbirth include power, passage, passenger, psychic and helper. Power is a very important factor in the process of childbirth, power can be controlled by pregnancy exercises. Pregnant exercise is an exercise to train the muscles so that they function optimally in normal childbirth. There were 92% of mothers who regularly had pregnancy exercise experienced a normal childbirth period and 8% were abnormal. The initial survey at Ernita's BPM found four mothers (66.7%) experiencing normal childbirth and there were two mothers (33.3%) experiencing abnormal childbirth, apparently the mother did not take pregnancy exercises. This study aims to determine the relationship between pregnancy exercise and normal childbirth BPM in Ernita Pekanbaru City Year 2018. Types of quantitative analytical research with retrospective design, Purposive sampling technique with a population of 46 people and 50 samples of respondents. The results of the study of mothers taking pregnancy exercise regularly experienced normal childbirth 26 people (52%) and 1 person (2%) were not normal. Based on the chi square test obtained p value 0.039 <α 0.05 means that there is a significant relationship between pregnancy gymnastics and normal childbirth. Suggestions for health agencies are expected to improve socialization about pregnancy exercise and apply to ANC services and in pregnant classes.